Semua Akan Mumet pada Waktunya dalam Kajian Pendidikan Islam - Salis Wahyu Hidayati; Robingun Suyud El Syam; Muhammad Saefullah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Qur’an is a source of life, but many people ignore religious values ​​in solving their life problems. This article aims to examine everything that will be limited in time in the study of Islamic education. This article is a literature review in a qualitative descriptive setting, with inductive analysis. The findings show that all humans cannot escape the tests of life according to their respective portions. Islam teaches that in problems there are rewards and wisdom for people who try to solve them and are patient with them. This study focuses on the importance of an optimistic attitude in undergoing life's trials and the best perspective on a problem. It is hoped that the results of this research will contribute to Islamic education.